1998
DOI: 10.1016/s0022-5223(98)70052-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival of patients with coronary artery disease and left ventricular dysfunction: Implications for the role of myocardial viability assessment in management decisions

Abstract: Patients with low ejection fraction and evidence of viable myocardium by positron emission tomography have improved survival and symptoms with coronary bypass grafting compared with medical therapy. In patients without evidence of viability, survival and symptom improvement with bypass grafting are apparent only among those patients with severe angina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
99
0
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(111 citation statements)
references
References 21 publications
(68 reference statements)
8
99
0
4
Order By: Relevance
“…In support of this, clinical studies have demonstrated an increased mortality when patients with hibernating myocardium are not revascularized, and the excess risk is largely related to sudden death. 8 This increased mortality is also seen in animal studies of chronic hibernating myocardium, in which the cumulative incidence of sudden death approaches 50% over 5 months. 9 We hypothesized that hibernating myocardium exhibits regional inhomogeneity in sympathetic innervation that arises from chronic repetitive ischemia distal to a critical coronary stenosis.…”
mentioning
confidence: 84%
“…In support of this, clinical studies have demonstrated an increased mortality when patients with hibernating myocardium are not revascularized, and the excess risk is largely related to sudden death. 8 This increased mortality is also seen in animal studies of chronic hibernating myocardium, in which the cumulative incidence of sudden death approaches 50% over 5 months. 9 We hypothesized that hibernating myocardium exhibits regional inhomogeneity in sympathetic innervation that arises from chronic repetitive ischemia distal to a critical coronary stenosis.…”
mentioning
confidence: 84%
“…В дополнение к этому, чем больше было число проксимальных стенозов, тем больше была польза хирургического вмешательства [456,460]. Наблюда-тельные исследования также подтверждают преиму-щества КШ в улучшении выживаемости у пациентов с двухсосудистым поражением при наличии тяжелой или протяженной ишемии или тяжелой стенокардии [197,[461][462][463][464]. Представления о выгодах реваскуля-ризации у пациентов с протяженной ишемией в настоящее время проверяются в исследовании ISCHEMIA (International Study of Comparative Health Effectiveness with Medical and Invasive Approaches) [197,214,465].…”
Section: операция в условиях искусственного кровообращения или без неunclassified
“…Recent data from the MONICA Project 3 relative to a 10-year period of study with 37 different populations indicate a reduction in ischemic cardiac events and related mortality rates in most countries. Multiple aspects have contributed to this favorable tendency, including the reduction in the prevalence of risk factors, the improvement in health care and the increase in access to it, and new methods of diagnosis and treatment 4,5 .The number of myocardial revascularization surgeries increased 227% in the United States from 1979States from to 1997States from , and, in 1997,000 patients underwent this surgical procedure. In that country, approximately 1 in every 1,000 individuals undergoes myocardial revascularization surgery per year, which results in costs of $ 50 billion an-…”
mentioning
confidence: 99%
“…Recent data from the MONICA Project 3 relative to a 10-year period of study with 37 different populations indicate a reduction in ischemic cardiac events and related mortality rates in most countries. Multiple aspects have contributed to this favorable tendency, including the reduction in the prevalence of risk factors, the improvement in health care and the increase in access to it, and new methods of diagnosis and treatment 4,5 .…”
mentioning
confidence: 99%